Putting violence against women into words: May ideology have an effect in audio description? - Puri Meseguer Cutillas; Marina Ramos Caro (Cadernos de Tradução, 2025)
This paper offers an exploratory approach to the role of ideology in translation and, specifically, in the audio description of a scene depicting violence against a woman. We performed a study in which translation students were asked to audio describe the wedding night scene between Khal Drogo and Daenerys Targaryen in Game of Thrones (Benioff & Weiss, 2011). We aimed to find out whether the audio descriptions produced by the students reflected objectively the violence contained in the scene and whether ideology could have any effect on the strategies used to reflect this violence. Results from the analysis revealed that despite a homogeneous sample (women, left-wing and feminist) predicting a tendency to make the violence of the scene visible, participants employed strategies aimed at softening and omitting any element that would suggest to the audience that rape was taking place.